Beyond cheap talk accounts: A theory of politeness in negotiations. (2021) - Lee, Alice J.; Mason, Malia F.; Malcomb, Claire S.
Abstract: Negotiations are a careful balancing act between cooperation and competition—a successful negotiation requires extracting maximal value without offending and alienating a counterpart (i.e., the negotiator's dilemma ). It is thus surprising that negotiation scholars have largely overlooked a pervasive feature of negotiations: they entail "polite" speech. In this paper, we introduce politeness as a communicative strategy that is critical to solving the negotiator's dilemma. By strategically adjusting their utterances to signal deference and respect, negotiators can make ambitious requests without derailing the exchange. Starting with an overview of politeness and a review of the relevant negotiation literature, we offer testable propositions regarding how attempts at polite speech manifest in negotiations, who is especially likely to express them, under what conditions, and to what effect. We also consider the conditions under which this communication strategy undermines negotiators. We hope our review and theorizing will open up broader discussions on the role of polite speech in deal making and conversational dynamics.